2012
DOI: 10.5402/2012/142313
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton-Associated Protein 4: Functions Beyond the Endoplasmic Reticulum in Physiology and Disease

Abstract: Cytoskeleton-associated protein 4 (CKAP4; also known as p63, CLIMP-63, or ERGIC-63) is a 63 kDa, reversibly palmitoylated and phosphorylated, type II transmembrane (TM) protein, originally identified as a resident of the endoplasmic reticulum (ER)/Golgi intermediate compartment (ERGIC). When localized to the ER, a major function of CKAP4 is to anchor rough ER to microtubules, organizing the overall structure of ER with respect to the microtubule network. There is also steadily accumulating evidence for diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…These data were further validated by quantitative real-time PCR (qRT–PCR) analysis of mRNA from KMS18 and KMS27 cells transfected with siRNA Deptor or siRNA negative control (Figure 3A and 3B ). Consistent with these results, western blot analysis from these cells revealed that Deptor depletion produced a significant reduction of ERLIN2, KEAP1, PSEN2 protein levels, with a concomitant increase of DERL3 amounts (Figure 3C ) [ 30 32 ]. In agreement, ectopic over-expression of Deptor in U266 cells, a MM cell line with low expression of this protein, produced an increase of ERLIN2, KEAP1 and CKAP4 protein levels with a concomitant decrease of DERL3 expression ( Supplementary Figure S1A ).…”
Section: Resultssupporting
confidence: 66%
“…These data were further validated by quantitative real-time PCR (qRT–PCR) analysis of mRNA from KMS18 and KMS27 cells transfected with siRNA Deptor or siRNA negative control (Figure 3A and 3B ). Consistent with these results, western blot analysis from these cells revealed that Deptor depletion produced a significant reduction of ERLIN2, KEAP1, PSEN2 protein levels, with a concomitant increase of DERL3 amounts (Figure 3C ) [ 30 32 ]. In agreement, ectopic over-expression of Deptor in U266 cells, a MM cell line with low expression of this protein, produced an increase of ERLIN2, KEAP1 and CKAP4 protein levels with a concomitant decrease of DERL3 expression ( Supplementary Figure S1A ).…”
Section: Resultssupporting
confidence: 66%
“…As shown in Figure 1H, all maytansinoid-based ADCs, including T-DM1, α-CD22-DM1, α-CD79b-DM1, and α-gD-DM4, bound to CKAP5, whereas brentuximab vedotin, an auristatin (a potent antimiotic agent)-based ADC, trastuzumab, pertuzumab, and control IgG failed to bind CKAP5. Figure 1I showed that both CKAP4, a type II transmembrane protein [29], and CKAP2 were unable to bind to T-DM1.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of CKAP4 reversed the miR-7-mediated effects on VSMCs. As the receptor of dickkopf-related protein 1 (DKK1), CKAP4 mediates downstream signaling to promote cellular proliferation and inhibit apoptosis through the activation of the PI3K/AKT pathway (27). Apoptosis of VSMCs is crucial for normal vascular remodeling (28).…”
Section: Discussionmentioning
confidence: 99%